The significance of staff development in improving quality education : a case study of three Hippo Valley Estates schools in Chiredzi District - Mudyiwa, Adonis (Midlands State University, 2020)
This study was on the significance of staff development in improving the quality education in three of the eight Hippo Valley Estates primary schools. Primary schools were targeted by the researcher because they provide the basic foundation in the education system. It is the quality aspect at this elementary stage that determines quality of the future. The descriptive survey was the research design used in the study. This design allows data collection for the purpose of making meaning out of it. The researcher used the following instruments: questionnaire, interviews and site visit. The questionnaires and interviews had similar questions here and there. The research instruments were pilot tested in three Hippo Valley Estates schools so as to ensure their validity and reliability during data collection. The researcher personally conducted the interviews and distributed the questionnaires in order to ensure hundred percent return of questionnaires. Teachers shared their experiences of the staff developments experiences they have received. Student achievement and its relationship to staff development was explored. Teachers discussed contributions staff development training do in improving quality education. The research findings proved that staff development programmes can improve quality education. This study could be of interest to school systems into the insights and needs of apprentice and veteran teachers. The results of this data can assist other schools with information to evaluate their current staff development programs and determine if changes should be made or not.